THE PROTECTIVE EFFECT OF THYMOL AGAINST CISPLATIN-INDUCED OTOTOXICITY: AN EXPERIMENTAL ANIMAL STUDY - (:unkn) unknown (My University, 2017)
Objective: The aim of this study is to investigate the protective effect of thymol against cisplatin- induced ototoxicity by evaluatingaudiological, biochemical and histopathological parameters.Materials and methods: Thirty-two male rats were divided into four groups (control, cisplatin, thymol + cisplatin and thymol) includingeight rats each. 150 mg/kg/day thymol was given for 5 days orally. Single dose cisplatin(16 mg/kg) was also given via intraperitoneal route.Distortion product otoacoustic emission(DPOAE) and auditory brainstem response(ABR) tests from both ears were performed in all groupsat the beginning of the study and also on days 6. Intracardiac blood samples and their cochleas were taken on day 6 for assessment ofbiochemical and histopathological(including TUNEL) parameters.Results: In audiological assessment, in group 2(cisplatin), there were significant decreases in DPOAE values and significant increases inABR thresholds on days 6 as compared with other groups. In Groups 1(control), 3(thymol + cisplatin) and 4(thymol) there was no significantdifference between the pre- and posttreatment DPOAE and ABR results.In biochemichal analyses, the total oxidant status(TOS) value was significantly higher in group 2(cisplatin) than in the other groups. Thetotal antioxidant status(TAS) value was significantly higher in group 3(thymol+cisplatin) than in group 2.In the histopathological examinations, there was significant reduction of the number of TUNEL-positive cells in the group3(thymol+cisplatin) compared to the group 2(cisplatin).Conclusions: The audiologic tests, biochemical results and histologic findings revealed that thymol may have protective effect againstcisplatin ototoxicity by increase antioxidant levels and reduce oxidative stress parameters.

Amaç: Bu çalışmanın amacı odyolojik, biyokimyasal ve histolojik parametreler ile timolün sisplatin ototoksisitesine karşı koruyucu etkisini araştırmaktır. Gereç ve yöntem: 32 sıçan 4 gruba ayrılmıştır(kontrol, sisplatin, timol+sisplatin, timol) 150 mg/kg/gün timol 5 gün süreyle oral yoldan, tek doz cisplatin(16 mg/kg) intraperitonel yolla verilmiştir. Sıçanlara çalışmanın başında ve 6. günde, Distortion product otoakustik emisyon(DPOAE) ve auditory brainstem response(ABR) testleri yapılmıştır. Biyokimyasal ve histolojik parametrelerin değerlendirilmesi için 6. Günde intrakardiyak kan örneklemesi yapılmıştır ve sıçan kokleaları diseke edilmiştir. Bulgular: Odyolojik değerlendirmede; grup 2(sisplatin)’de 6. günde, DPOAE değerlerinde anlamlı düşme ve ABR değerlerinde anlamlı yükselme görülmüştür. Grup 1(kontrol), grup3(timol+sisplatin) ve grup 4(timol)’ de tedavi öncesi ve sonrası DPOAE ve ABR değerlerinde anlamlı fark yoktur. Biyokimyasal Analizde; diğer gruplara göre grup 2(sisplatin)’de total oxidant status(TOS) değeri anlamlı olarak yüksektir. Grup 3(timol+sisplatin)’ de total antioxidant status(TAS) değeri grup 2(sisplatin)’ye göre yüksek olarak bulundu. Histopatolojik muayenede; Grup 3(timol+sisplatin)’ de TUNEL pozitif hücre sayısı grup 2(sisplatin)’ye göre azalmış olarak bulundu. Sonuç: Odyolojik testler, biyokimyasal sonuçlar ve histolojik bulgular timolün sisplatin ototoksisitesine karşı koruyucu etki gösterebileceğini göstermiştir.
TİMOLÜN SİSPLATİN OTOTOKSİSİTESİNE KARŞI KORUYUCU ETKİSİ: DENEYSEL HAYVAN ÇALIŞMASI
Keywords: Kulak, Burun, Boğaz